Hubungan Partisipasi Program Sekolah Perempuan Dengan Resiliensi Perempuan Kepala Keluarga di Kecamatan Lakarsantri Kota Surabaya - Angelia Anjani Telaum Banua; Wiwin Yulianingsih (J+PLUS UNESA, 2026)
Women-headed households (PEKKA) are vulnerable to various economic, social, and psychological pressures, so they need the ability to cope with daily life. One form of non-formal education is the Women’s School Program (SEKOPER), which helps build women’s capacity, independence, and resilience in facing various challenges. This program provides women not only with practical skills but also with mental and social empowerment that helps them become stronger. This study aims to analyze the significance of the relationship between the SEKOPER Program and resilience as empirical evidence of the effectiveness of community-based non-formal education in enhancing the psychosocial resilience of female heads of households. This study employed a quantitative approach, specifically a correlational study. The sample consisted of 50 participants who were actively involved in the SEKOPER Program and had passed validity and reliability tests. Pearson’s product-moment correlation and SPSS were used to analyze the data. The results of the study indicate a positive and significant correlation between participation in the SEKOPER Program and the level of resilience among PEKKA members in Lakarsantri Subdistrict (r = 0.639; p = 0.000). These findings suggest that PEKKA members who participate more actively in the SEKOPER Program tend to have higher levels of resilience. The SEKOPER Program has demonstrated that it not only helps people acquire skills and become more self-reliant, but also helps women maintain their psychosocial resilience when facing various life challenges.